The effects of zinc(II)phthalocyanine photosensitizers on biological activities of epitheloid cervix carcinoma cells and precise determination of absorbed fluence at a specific wavelength - Yurttas, Asiye Gok; Sevim, Altug Mert; Cinar, Kamil; Atmaca, Goknur Yasa; Erdogmus, Ali; Gul, Ahmet (ELSEVIER SCI LTD, 2022)
Photodynamic therapy (PDT) is an alternative way to treat the cancer non-surgically with minimum harm, in which a specific light and light sensitive photosensitizer (PS) is used. This study deals with the utilization of zinc photosensitizers (lambda(max) similar to 700 nm) from the group of phthalocyanines in photodynamic therapy. The photosensitizers differed in bearing either tetra-or octa-mercaptopropionic acid groups. The phthalocyanines (L1ZnPc and DipZnPc) were tested in cancer cell line, HeLa cell (epitheloid cervix carcinoma), by dark and light cytotoxicity. The photophysico-chemical properties of the resulting zinc photosensitizers were analyzed and to investigate the singlet oxygen's efficiency, photochemical properties were determined. For L1ZnPc, the singlet oxygen quantum yield was Phi(Delta) = 0.41 and for DipZnPc, the value was Phi(Delta) = 0.27. In addition to the experimental outcomes, this study handles detailed calculations of the absorbed light dose by the photosensitizer at a specific wavelength. In the light of this study, the researchers could get the insight of the precise amount of energy delivered to the cells by a laser beam for critical applications. The absorbed dose of the laser irradiation was calculated within a true wavelength range that is the most detailed explanation in literature.
Keywords: Phthalocyanine; Photodynamic therapy; Dark cytotoxicity; Light cytotoxicity; Absorbed fluence; Laser fluence; WATER-SOLUBLE PHTHALOCYANINES; IN-VITRO; PHOTOPHYSICAL PROPERTIES; ACID; ZINC; NANOPARTICLES; SUBSTITUENTS; MECHANISMS; FEATURES; Chemistry; Engineering; Materials Science